Ritual Child Homicide in Contemporary Africa: A Systematic Review of the Empirical Literature - Owusu, Emmanuel Sarpong (International criminal justice review, 2025)
Ritual child homicide, the killing of children for ritual or occult purposes, is a phenomenon that occurs in many African countries. Prior to the 21st century, very little, if any, criminological analysis of ritual paedicide in African settings existed. However, research on ritual child homicide has increased in recent years, leading to greater knowledge and understanding of the phenomenon. The present study sought to consolidate and synthesize information on ritual child homicide in African communities to facilitate a better appreciation of the phenomenon. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, a comprehensive search for empirical studies on ritual paedicide in African settings, spanning the years 2000 to 2022, was conducted across four databases: Scopus, Web of Science, Journal Storage, and Google Scholar. A total of 14 studies met the eligibility criteria and were diligently appraised. The review shows that most ritual paedicide victims are from families of low socioeconomic backgrounds in rural communities. A ritual paedicide typically involves multiple culprits. The actual perpetrators (i.e., body hunters or murderers) are predominantly males of low socioeconomic status, motivated largely by monetary gain. To combat the phenomenon, economic improvement, the promotion of formal and public education, formal regulation of the activities of traditional healers/spiritualists, and the strengthening of the criminal justice system are recommended.